PROFESSIONAL ENGLISH IN HIGHER EDUCATION - Pershakov, Valeriy; Pylypenko, Oleksandr; Akmaldinova, Oleksandra; Burlay, Vitaliy (Proceedings of National Aviation University (archive), 2020)
The issue of ESP teaching at Ukraine higher education institutions is dealt with in the context of integration into the European educational space. Analysis of current situation in the field of professional foreign language teaching in some universities and possible ways to raise the level of training graduates of technical specialties with proper foreign language competence are presented.